Environmental and social performance disclosure and shareholders’ wealth- a perspective from Malaysian companies - Khaveh, Amir; Nikhashemi, Seyed Rajab; Yousefi, Abdolaziz; Haque, A. K. M. Ahasanul (New South Wales Research Centre Australia (NSWRCA), 2012)

(untitled)
Since sustainability reporting is a mean to communicate with a wide range of internal and external stakeholders and also reflect the companies’ sustainability performance, which inspires sustainable growth and development, consequently increasingly more and more stakeholders including shareholders ask for sustainability disclosures. In some Countries CSR reporting has become mandatory by legislation and companies have to disclose their environmental and social activities. Sustainability reporting has become mandatory for Malaysian public listed companies (PLC) since 2007. There a declarative about CSR activities in all Malaysian companies but number of sustainability indicators and the quality of disclosure are different among different companies. Since the main goal of each business is to maximize its shareholders’ wealth, and CSR practices would occur costs for companies, this paper amis to find any significant relationship between level of CSR disclosure and companies share price and net profit. The result. The paper studied through 45 Malaysian public listed companies in three years (From 2008-2010). The results indicated that companies with higher level of sustainability disclosure have higher share price and have higher net profit